2014
DOI: 10.1038/cdd.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of miR-197 targeting in p53 wild-type lung cancer

Abstract: Lung cancer is the leading cause of tumor-related death. The lack of effective treatments urges the development of new therapeutic approaches able to selectively kill cancer cells. The connection between aberrant microRNA (miRNA -miR) expression and tumor progression suggests a new strategy to fight cancer by interfering with miRNA function. In this regard, LNAs (locked nucleic acids) have proven to be very promising candidates for miRNA neutralization. Here, we employed an LNA-based anti-miR library in a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 39 publications
4
77
0
Order By: Relevance
“…mirNa-197 overexpression is a potential biomarker for early detection of lung cancers and also correlates with metastasis 34 . elevated mir-197 expression is correlated with reduced Fus1 expression in Nsclc tumour, confirming that mir-197 targets the 3`UTr of the Fus1 transcript 35 and with reduced p53 tumour suppressor gene 36 . FUs1 induces apoptosis through the activation of the intrinsic mitochondrial-dependent and apaf-1-associated pathways and inhibits the function of protein tyrosine kinases including eGFr and aKT among others, in lung cancer 37 .…”
Section: The Role Of Mirnas In Brain Metastasissupporting
confidence: 54%
See 1 more Smart Citation
“…mirNa-197 overexpression is a potential biomarker for early detection of lung cancers and also correlates with metastasis 34 . elevated mir-197 expression is correlated with reduced Fus1 expression in Nsclc tumour, confirming that mir-197 targets the 3`UTr of the Fus1 transcript 35 and with reduced p53 tumour suppressor gene 36 . FUs1 induces apoptosis through the activation of the intrinsic mitochondrial-dependent and apaf-1-associated pathways and inhibits the function of protein tyrosine kinases including eGFr and aKT among others, in lung cancer 37 .…”
Section: The Role Of Mirnas In Brain Metastasissupporting
confidence: 54%
“…FUs1 induces apoptosis through the activation of the intrinsic mitochondrial-dependent and apaf-1-associated pathways and inhibits the function of protein tyrosine kinases including eGFr and aKT among others, in lung cancer 37 . inhibition of mir-197 promotes upregulation of p53-dependent apoptosis in lung cancers 36 . mir-184 suppresses cell proliferation by modulating cell cycle transition signals such as c-myc, blocking cell growth mediated by pi3K/aKT/c-Jun pathway.…”
Section: The Role Of Mirnas In Brain Metastasismentioning
confidence: 99%
“…Recently, miR-197 has been identified as an oncomiR in hepatocellular carcinoma [20], non-small-cell lung cancer [21], pancreatic cancer [22] and male breast cancer [23]. However, other studies revealed that miR-197 was down-regulated in esophageal cancer [24], oral carcinoma [25], gastric carcinoma [26], osteosarcoma [27] and astrocytomas [28], and might exert an anti-cancer effect on these cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Given that miR-197 transfection barely reduced cell proliferation, cell growth arrest does not seem to be involved in the effects of this miRNA at 5 nM (Fig. 2D) (26). Collectively, these data indicate that the expression of miR-197 is disadvantageous for EV71 replication and that the virus may escape such suppression by downregulating the cellular miR-197 levels.…”
Section: Resultsmentioning
confidence: 65%